Power to Teach - Robinson, Wendy (Woburn Education Series, 2004)
This book illustrates hitherto unexamined connections between the present state of teacher education in the UK and past models of practice. It locates contemporary debates within ongoing historical tensions over what constitutes a sound and proper start to a career in teaching. Questions as to the constituents of a professional training, the essential skills, knowledge and attitudes desired of an effective teacher, the most suitable locus of expertise, the relative roles of participants, and the balance of theory and practice lie at the heart of this book. The book reviews apprenticeship and teach-exemplar models of training, expert-novice relationships, model and demonstration teaching, school-based practice and the elaboration of core pedagogical principles in educational debate and research. These developments are assessed against recent initiatives in ITT, such as partnership models of ITT, school-based mentoring, advanced skills teaching, training schools, a standards-driven model of assessment for student teachers and models of effective teaching. Central to the book is the concept of the power to teach. By reclaiming this notion, the book offers challenging new perspectives on current policy and practice in teacher education today and adds to existing histories of teacher training of the past.